2020
DOI: 10.5194/se-11-1643-2020
|View full text |Cite
|
Sign up to set email alerts
|

Transverse jointing in foreland fold-and-thrust belts: a remote sensing analysis in the eastern Pyrenees

Abstract: Abstract. Joint systems in the eastern portion of the Ebro Basin of the eastern Pyrenees enjoy near continuous exposure from the frontal portion of the belt up to the external portion of its associated foredeep. Utilizing orthophoto mosaics of these world-class exposures, we have manually digitized over 30 000 joints within a 16 km×50 km study area. The mapped traces exhibit orientations that are dominantly perpendicular to the trend of the belt (transverse) and, subordinately, parallel to the belt (longitudin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Low amount of N-S major and secondary normal faults suggests that N-S faulting is not the main process controlling the formation of N-S fractures (Figure 3e). N-S fractures have been described north of Conflent by Arthaud and Pistre [1993] and are commonly attributed to the N-S Pyrenean compression Mattauer, 1969, 1972;Ballas et al, 2012;Tavani et al, 2020]. Where N-S fractures clusters are observed (e.g.…”
Section: N-s Fractures As Part Of the Background Fracturingmentioning
confidence: 99%
“…Low amount of N-S major and secondary normal faults suggests that N-S faulting is not the main process controlling the formation of N-S fractures (Figure 3e). N-S fractures have been described north of Conflent by Arthaud and Pistre [1993] and are commonly attributed to the N-S Pyrenean compression Mattauer, 1969, 1972;Ballas et al, 2012;Tavani et al, 2020]. Where N-S fractures clusters are observed (e.g.…”
Section: N-s Fractures As Part Of the Background Fracturingmentioning
confidence: 99%
“…A second possible explanation for crossjoints is that they accommodated along-foredeep stretching due to cross-sectional (e.g. Tavani et al 2020) and/or planar (e.g. Doglioni, 1995) arching of the foredeep.…”
Section: B Tectonic Evolution Of the Study Areamentioning
confidence: 99%
“…The presence of joints and veins in the 'undeformed' foreland of fold-and-thrust belts (e.g. Dunne & North, 1990;Railsback & Andrews, 1995;Zhao & Jacobi, 1997;Billi & Salvini, 2003;Whitaker & Engelder, 2006;Martinelli et al 2019;Tavani et al 2020) suggests, however, that several joints and veins observed on anticlines of accretionary wedges might have developed before folding, i.e. during foreland deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The narrow southeastern fold-thrust belt is propagated through primarily syn-orogenic Upper Cretaceous to earliest Oligocene strata of the flexural foreland Ebro basin (Muñoz et al, 1988;Tavani et al, 2020;Vergés et al, 1995;Verges et al, 1998) (Figure 4). The oldest synorogenic sediments found in the eastern portion of the Ebro basin, found only at the northern margin of the basin, are Maastrichtian-Paleocene Garumnian-facies continental siltstones and shallow marine carbonates.…”
Section: Pyrenees Introductionmentioning
confidence: 99%